(3MGTjI Ydi gOGjI GdMceIs - (3eUdM GdOjf eMeO Hf UdGM Hf LdGd GdedJhi GddGQis; (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s ((3eUWai GdSYjO s)
(3ChdgG (B:s
(3hHYO jbhd CabQ GdNdb eMeO GdeOYh HeUdM GdOjf GddGQi GdCfUGQi s
(3BNQgG (B:s
(3ai SGFQ GdCLSGe gPG GdEYJHGQ eHfi Ydi GdCehQ GdYQajI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeQcRjI GdYGeI (B_ (3GdehUd s
Keywords: (3GdadSaI hGdefWbs